2006
DOI: 10.2174/138161206777698909
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and Human Cognitive Performance

Abstract: In the past decade, experimental studies involving healthy human volunteers have revealed that manipulations of the central serotonin (5-HT) system can produce quite specific changes in cognitive functioning, independent of overt mood changes. Reduced 5-HT turnover is consistently associated with impaired long-term memory functioning. Low 5-HT function may also impair cognitive flexibility and improve focused attention. On the other hand, stimulation of central 5-HT has repeatedly been found to impair performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
149
1
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(159 citation statements)
references
References 126 publications
(183 reference statements)
4
149
1
5
Order By: Relevance
“…Mood may be improved in depressed cognitively impaired older patients by treatment with antidepressants including selective serotonin reuptake inhibitors (SSRI) even in the absence of improvement in cognitive or motor domains (Schrag 2006;Ishihara and Brayne, 2006;Nebes et al, 2003). The actions of serotonin in the development and treatment of impairments seen in neurodegenerative diseases require further investigation (Gruden et al, 2007;Schmitt et al, 2006;Truchot et al, 2007).…”
Section: Possible Relevance Of 5-htt Axon Degeneration To Symptoms Ofmentioning
confidence: 99%
“…Mood may be improved in depressed cognitively impaired older patients by treatment with antidepressants including selective serotonin reuptake inhibitors (SSRI) even in the absence of improvement in cognitive or motor domains (Schrag 2006;Ishihara and Brayne, 2006;Nebes et al, 2003). The actions of serotonin in the development and treatment of impairments seen in neurodegenerative diseases require further investigation (Gruden et al, 2007;Schmitt et al, 2006;Truchot et al, 2007).…”
Section: Possible Relevance Of 5-htt Axon Degeneration To Symptoms Ofmentioning
confidence: 99%
“…Whereas consolidation of new information into long-term memory appeared to be compromised by a reduction of central 5-HT activity; shortterm memory functions were intact. Several studies have subsequently confirmed that 5-HT is specifically involved in long-term memory functioning (for review, see Sambeth et al 2007;Schmitt et al 2006). Interestingly, ATD did not affect long-term memory retrieval or recognition when the depletion was induced after learning and consolidation of a word list (Schmitt et al 2000).…”
Section: Introductionmentioning
confidence: 98%
“…The introduction of fluoxetine (Prozac) and other selective serotonin reuptake inhibitors (SSRIs) has changed the treatment of depressive disorders (Wong et al, 1974;Wong et al, 1995) through acute and chronic effects (Lucki, 1998;Hoyer et al, 2002;Schmitt et al, 2006;Cools et al, 2008;Arnsten, 2009). The chemical hypothesis of depression emphasizes that the imbalance in the function of the serotonergic system is reinstated by SSRIs by elevating serotonin (5-HT) levels (Maes and Meltzer, 1995;Manji et al, 2001;Castrén, 2005), but alternative hypotheses have also been proposed (Lacasse and Leo, 2005;Nestler, 2008, 2010;Luscher et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Humans (Harmer et al, 2003;Schmitt et al, 2006) and animals (Clarke et al, 2004;Brigman et al, 2010) display altered cognitive performance after having their central 5-HT level experimentally manipulated. With limited studies performed on human pyramidal cells (McCormick and Williamson, 1989;Newberry et al, 1999), our current knowledge about synaptic mechanisms of 5-HT in the cortex is based on non-human in vitro experiments in which micromolar concentrations of 5-HT were applied (Andrade and Nicoll, 1987;Aghajanian and Marek, 1997;Schmitz et al, 1998b;Ciranna, 2006;Zhong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%